Exploring Learning for On-Campus Students Transitioning to Online Learning during the COVID-19 Pandemic: Perceptions of Students in the Higher Education - Oluyomi Abayomi Osobajo; Adekunle Oke (Education Sciences, 2022)
Due to the emergence of COVID-19, the education sector has embraced online learning as the main delivery method to engage and impact knowledge and skills acquisition of their students. However, learning is not just about knowledge and skills acquisition but is an activity contributing to change and enrichment of the learner. This paper draws upon the results of a qualitative interview conducted amongst postgraduate students enrolled in an AMBA-accredited and top business school in the UK. The results revealed that students’ experience of the sudden transition to online learning is shaped by four distinct but interrelated areas: benefits of online learning, challenges of online learning, success factors in online learning and support in online learning. These findings will help higher education institutions and online learning tutors concentrate more on areas important to student learning when migrating from face-to-face to online modes of teaching.